Investigating teacher candidates’ perceptions of collaboration during a co-teaching experience - Brown, Corine Meredith; Viator, Martha Graham (Advances in Social Sciences Research Journal, 2019)
While teacher candidates learn the theoretical value of instructional collaboration in teacher preparation programs, they often lack professional preparation experiences to develop collaborative skills as educators in the classroom. To address this need, some teacher education programs have integrated co-teaching as part of their required clinical practice experiences. This case study research design examines two teacher candidates’ perceptions of collaboration as they engaged in co-planning and co-teaching in a secondary level, social studies classroom. Qualitative data sources including semi-structured interviews, co-planning sessions, field notes, formal classroom observations, and candidate-created lesson plans were collected. Case study data were coded for both patterns of coherence and contradictions throughout the analysis. Four major themes emerging from the data included co-planning, co-teaching, support systems, and division of labor. Qualitative analysis of the data revealed these pre-service teachers shared similar positive perceptions regarding co-planning constructs, skills, and activities. Yet both participants struggled with individual issues of competition within the classroom, as well as personal and professional confidence as instructors, creating mixed perceptions of collaboration in co-teaching.